Efficiency Performance Analysis of Mining Companies Listed in Sharia and Non-Sharia Stock Index in Indonesia with Data Envelopment Analysis (DEA) Method - Mauliani, Mauliani; Mukhsin, Moh.; Pardiansyah, Elif (FEB Universitas Sultan Ageng Tirtayasa, 2025)
The emergence of the mining industry in an area has a positive impact on the socio-economic life of the community there, especially in the mining community concession areas. Indonesia's mining sector plays an important role in the country's economy, contributing greatly to state revenues and job creation. The mining sector experienced a decline in 2020 due to the COVID-19 pandemic which also had an impact on Indonesia's GDP, resulting in a growth contraction of minus 2.07% compared to the previous year (BPS, 2021). This study aims to determine the efficiency performance of mining companies listed on the Indonesian Sharia Stock Index (ISSI) and mining companies listed on the LQ45 Index, and also to determine how the efficiency of the two compares. The data used in this study are panel data with 4 selected companies from a total ISSI sample of 22 companies and 4 selected companies from a total LQ45 sample of 11 companies. This study uses a non-parametric method, namely Data Envelopment Analysis (DEA), then a normality test is carried out with the Kolmogorov Smirnov-Test to determine whether the data is normally distributed or not. And the Mann Whitney U-Test was conducted to determine the significance of the differences in the efficiency levels of mining companies listed on ISSI and LQ45. The results of the study showed that the efficiency performance of mining companies listed on ISSI showed imperfect efficiency of 81%, the efficiency performance of mining companies listed on LQ45 also showed imperfect efficiency of 66%. While the comparison of efficiency between the two showed a significant difference seen based on the mean rank which showed the average value of ISSI mining company efficiency of 91.87, which was greater than LQ45 mining companies with a value of 69.13